Monitoring molecular dynamics of bacterial cellulose composites reinforced with graphene oxide by carboxymethyl cellulose addition - Sanchis M.J. (2017)
This work was supported by the DGCYT [MAT2015-63955-R]; the Vice-Rectorate for Research of the Pontificia Universidad Católica del Perú and the National Council of Science, Technology and Technological Innovation of Peru (CONCYTEC/FONDECYT).